2004
DOI: 10.1207/s15327663jcp1404_9
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Validity of the Implicit Association Test in Studies of Brands, Consumer Attitudes, and Behavior

Abstract: Three studies investigated implicit brand attitudes and their relation to explicit attitudes, product usage, and product differentiation. Implicit attitudes were measured using the Implicit Association Test (IAT; Greenwald, McGhee, & Schwartz, 1998). Study 1 showed expected differences in implicit attitudes between users of two leading yogurt brands, also revealing significant correlations between IAT‐measured implicit attitudes and explicit attitudes. In Study 2, users of two fast food restaurants (McDona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
213
2
26

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 306 publications
(263 citation statements)
references
References 29 publications
4
213
2
26
Order By: Relevance
“…In many cases, the measurement of a person's attitude that best predicts their behavior is done using an implicit test. By contrast, an explicit test is more vulnerable to the influence of experimenter demand (Orne, 1962) and socially appropriate responding (Greenwald, Poehlman, Uhlmann, & Banaji, 2009;Maison, Greenwald, & Bruin, 2004) and to the limitations of consciously accessible decision processes (Dijksterhuis, 2004). Having observed the greater reliability and validity of indirect measurement of search ability in person perception ratings, it will be important in future research to determine which visible behaviors underlie these less reliable ratings of search ability.…”
Section: Resultsmentioning
confidence: 99%
“…In many cases, the measurement of a person's attitude that best predicts their behavior is done using an implicit test. By contrast, an explicit test is more vulnerable to the influence of experimenter demand (Orne, 1962) and socially appropriate responding (Greenwald, Poehlman, Uhlmann, & Banaji, 2009;Maison, Greenwald, & Bruin, 2004) and to the limitations of consciously accessible decision processes (Dijksterhuis, 2004). Having observed the greater reliability and validity of indirect measurement of search ability in person perception ratings, it will be important in future research to determine which visible behaviors underlie these less reliable ratings of search ability.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Brunel, Tietje, and Greenwald (2004) found that implicit measures can be useful in predicting brand recognition and preference, as well as product usage, above and beyond traditional explicit measures. Similarly, Maison, Greenwald, and Bruin (2004) showed that implicit measures can successfully discriminate consumers' preferences for different competing brands. Petty, Fazio, and Briñol (2009b) articulated three different meanings that have been applied to defining implicit attitude measures: indirect, automatic, and unconscious.…”
mentioning
confidence: 99%
“…During the past decade, a major development in this research has been the introduction of so-called implicit measures. These measures were originally put forward mainly within the social psychology literature (e.g., Fazio, Jackson, Dunton, & Williams, 1995;Greenwald, McGhee, & Schwartz, 1998) but have since then spread to various other subdisciplines of psychology, including differential psychology (e.g., Asendorpf, Banse, & Mücke, 2002), clinical psychology (e.g., Gemar, Segal, Sagrati, & Kennedy, 2001, consumer psychology (e.g., Maison, Greenwald, & Bruin, 2004), and health psychology (e.g., Wiers, van Woerden, Smulders, & de Jong, 2002).Despite the widespread use of implicit measures, the actual meaning of the term implicit measure is rarely defined. On the basis of the work of Borsboom (Borsboom, 2006;Borsboom, Mellenbergh, & van Heerden, 2004) and De Houwer (De Houwer, 2006;, we first provide a normative analysis of the concept "implicit measure."…”
mentioning
confidence: 99%